Child's play: illustrated bodies and traces of disability. Issue 5 (28th July 2016) - Lacey, Eve
ABSTRACT: This article examines traces of disability in children's literature, interrogating the opportunities for readerly play through which the child and the text may formulate character and plot in tandem. It focuses on instances of ellipsis and writing on the body in the works of David Almond and Jacqueline Wilson, and lauds the dependency of the incomplete, excessive or 'crip' text. Just as queer and critical disability theory reveal the cultural construction of bodies, so too texts come into being through a series of social, technical and infrastructural supports. The article explores obstacles to the articulation of illness and literary techniques to overcome that silencing stigma, to express the unutterable and so lift the quarantine between the sick subjects and their readers. A close examination of missing text and tattoos on fictional bodies reveals the ways in which authors foster a culture of interdependency in storytelling, in which the plot occurs at the intersection between reader and writer, and so disassemble the illusion of a self-sufficient body of work. The fragmented text makes plain this mutual dependency and so functions as a narrative prosthesis which figures the child reader as implicated in, rather than immune to, the stories of disabled characters.